Datamama, bringing pregnancy research into the future: design, development, and evaluation of a citizen science pregnancy mobile application - Eva Gerbier; Yvan Vial; Jardena Puder; Olivier Le Dizès; Magali Andrey; Amar Arhab; Antje Horsch; Antje Horsch; Valérie Avignon; Déborah Fort; Camille Deforges; Céline J. Fischer Fumeaux; et al. (Frontiers Media S.A., 2023)
Background: Pregnancy mobile applications (apps) have grown in popularity over the past decade, with some being used to promote study recruitment or health behaviors. However, no app serves as an all-in-one solution for collecting general data for research purposes and providing women with useful and desirable features.Aim: To create and develop a Swiss pregnancy mobile app as an innovative means to collect research data and provide users with reliable information.Methods: Determining the key features of the app involved a review of the literature and assessment of popular apps in the Swiss AppStore. A team of engineers developed the app, which includes a pregnancy timeline, questionnaires for data collection, medical and psychological articles and a checklist with appointment reminders. The content was written and reviewed by healthcare providers considered experts in the topics adressed. The questionnaires are distributed based on the user's gestational age, by a chatbot. The project was authorized by the ethics commission in the canton of Vaud. An online survey of ten questions, advertised on Datamama's home screen, was conducted to assess the users' use of the app (27.11- 19.12.2022).Results: A review of 84 articles and 25 popular apps showed the need for a comprehensive pregnancy app. The development of Datamama took 2 years and included the creation of 70 medical and psychological articles and 29 questionnaires covering 300 unique variables. Six months after the launch, there were 800 users with a 73% average participation rate in the questionnaires. Sixty-five women completed the survey, with 70.8% using the app once to multiple times per week. The primary reason for using the app was to help research by answering the questionnaires, followed by access to reliable medical information. The reason most frequently ranked first for using the app was to help research by answering the questionnaires (42/65, 67% of women rated it first), followed by access to reliable medical information (34/65, 54% women rated it second). Women rated the information as clear, understandable, and interesting with a trust rating in data handling at 98.5%. The average grade for recommending the app was 8/10, with suggestions for increasing the amount of medical content and tailoring it based on gestational age.Conclusion: Datamama is the first pregnancy app to address the needs of both patients and researchers. Initial feedback from users was positive, highlighting future challenges for success. Future work will consist in improving the app, validating the data and use it to answer specific pregnancy-related research questions.